Evidence of SARS-CoV-2 Related Coronaviruses Circulating in Sunda pangolins (Manis javanica) Confiscated From the Illegal Wildlife Trade in Viet Nam - Nga, Nguyen Thi Thanh; Latinne, Alice; Thuy, Hoang Bich; Long, Nguyen Van; Ngoc, Pham Thi Bich; Anh, Nguyen Thi Lan; Thai, Nguyen Van; Phuong, Tran Quang; Thai, Hoang Van; Hai, Lam Kim; Long, Pham Thanh; Phuong, Nguyen Thanh; et al. (Frontiers in Public Health, 2022)
ABSTRACT Despite the discovery of several closely related viruses in bats, the direct evolutionary progenitor of SARS-CoV-2 has not yet been identified. In this study, we investigated potential animal sources of SARS-related coronaviruses using archived specimens from Sunda pangolins (Manis javanica) and Chinese pangolins (Manis pentadactyla) confiscated from the illegal wildlife trade, and from common palm civets (Paradoxurus hermaphroditus) raised on wildlife farms in Viet Nam. A total of 696 pangolin and civet specimens were screened for the presence of viral RNA from five zoonotic viral families and from Sarbecoviruses using primers specifically designed for pangolin coronaviruses. We also performed a curated data collection of media reports of wildlife confiscation events involving pangolins in Viet Nam between January 2016 and December 2020, to illustrate the global pangolin supply chain in the context of Viet Nam where the trade confiscated pangolins were sampled for this study. All specimens from pangolins and civets sampled along the wildlife supply chains between February 2017 and July 2018, in Viet Nam and tested with conventional PCR assays designed to detect flavivirus, paramyxovirus, filovirus, coronavirus, and orthomyxovirus RNA were negative. Civet samples were also negative for Sarbecoviruses, but 12 specimens from seven live pangolins confiscated in Hung Yen province, northern Viet Nam, in 2018 were positive for Sarbecoviruses. Our phylogenetic trees based on two fragments of the RdRp gene revealed that the Sarbecoviruses identified in these pangolins were closely related to pangolin coronaviruses detected in pangolins confiscated from the illegal wildlife trade in Yunnan and Guangxi provinces, China. Our curated data collection of media reports of wildlife confiscation events involving pangolins in Viet Nam between January 2016 and December 2020, reflected what is known about pangolin trafficking globally. Pangolins confiscated in Viet Nam were largely in transit, moving toward downstream consumers in China. Confiscations included pangolin scales sourced originally from Africa (and African species of pangolins), or pangolin carcasses and live pangolins native to Southeast Asia (predominately the Sunda pangolin) sourced from neighboring range countries and moving through Viet Nam towards provinces bordering China.